Re-aligning research into teacher education for CALL and bringing it into the mainstream. (July 2014) - Motteram, Gary
<x content-type="archive" xml:space="preserve">Abstract</x> This paper explores three research projects conducted by the writer and others with a view to demonstrating the importance of effective theory and methodology in the analysis of teaching situations where Computer Assisted Language Learning (CALL), teacher practice and teacher education meet. It argues that there is a tendency in the field of teacher education for CALL to make use of what might be considered quite traditional research methodology, often drawing on research traditions not connected to teacher education. In teacher education and CALL, research theory is quite often drawn from the field of Second Language Acquisition (SLA), which despite its connection with CALL, is less relevant to the specific combined demands of researching teacher education for CALL. At the same time we are seeing some moves in recent publications and conference presentations towards the use of sociocultural theories as part of an analysis of CALL teacher practices and teacher education for CALL. In this paper, I argue that this is a positive step in the direction of establishing teacher education for CALL as a more mature field of enquiry. In order to avoid the pitfalls of inappropriate research methodology, the paper then presents an argument for a range of methodologies, chosen on the basis of a fashioning of research instruments (Czarniawska 1998), or a 'bricolage' (Levi-Strauss 1962/1966) that enables us – in conjunction with the theory – to explore different teaching situations in an informed and effective way.